2020
DOI: 10.1109/access.2020.2996713
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Data-Driven Fault Feature Separation Method and Its Application on Intelligent Fault Diagnosis Under Variable Working Conditions

Abstract: As mechanical fault diagnosis enters the era of big data, the traditional fault diagnosis methods under variable working condition are difficult to be applied because of the massive computation cost and excessive reliance on human labor. For the application of intelligent fault diagnosis under variable working conditions, the crucial difficulty is that the variable speed or load can cause smearing and skewing of classable feature. It is the key to break the predicaments by extracting the features which are irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…One is normal data, denoted as N; the other three types of data are fault data, namely roller fault, inner race fault and outer race fault denoted RF, and OF. Among them, for each type we took faults with different damage degrees (7,14 and 21 Mils). Therefore, the above can be summarized as we have a total of ten different types of data, which are simply labeled N, RF1, RF2, RF3, IF1, IF2, IF3, OF1, OF2, OF3, corresponding to the ten kinds of category labels (C0-C9).…”
Section: Experimental Verification On Open Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…One is normal data, denoted as N; the other three types of data are fault data, namely roller fault, inner race fault and outer race fault denoted RF, and OF. Among them, for each type we took faults with different damage degrees (7,14 and 21 Mils). Therefore, the above can be summarized as we have a total of ten different types of data, which are simply labeled N, RF1, RF2, RF3, IF1, IF2, IF3, OF1, OF2, OF3, corresponding to the ten kinds of category labels (C0-C9).…”
Section: Experimental Verification On Open Datasetmentioning
confidence: 99%
“…At the same time, with the development of networks, information technology and various monitoring technologies, the data generated by mechanical equipment shows exponential growth [4,5]. The traditional fault diagnosis method is unable to cope with such a huge amount of data due to its own disadvantages, so the intelligent fault diagnosis method emerged [6,7]. The intelligent fault diagnosis method is expected to overcome some difficulties that exist in traditional fault diagnosis methods and solve the problem of complex system fault diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [25] proposed a deep subdomain adaptation network (DSAN) to extract features of multiscale vibration signals using local maximum mean discrepancy (LMMD) loss to reduce the distance between source and target domains and achieve transfer diagnosis of wind turbine system faults. Li et al [26] introduced an adversarial DA method based on conditional adversarial DA (CDAN), which enforces better intraclass compactness and interclass separability of labelrelated prediction results to improve model generalization, enabling transfer diagnosis of typical bearing faults under variable conditions. The above studies have shown that constructing feature distribution constraint functions effectively obtains domain-invariant features under variable operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al [22]constructed a multimode CNN model to improve the fault detection accuracy of rolling bearings under variable working conditions. Li et al [23] proposed a data-driven fault feature separation method to eliminate the working condition information and extract the precise classable feature for fault diagnosis. Su et al [24]proposed a hierarchical branch CNN scheme that considered polluted data and variations in the working environment conditions.…”
Section: Introductionmentioning
confidence: 99%